Trazabilidad mediante blockchain en el sistema de ventas de obras de arte de la carrera de artes plásticas - Vicente Jimenez, Alexander Adrian (2025)
In recent years, the online art market has experienced exponential growth, allowing artists to exhibit and market their works of art through a multitude of digital platforms. Nevertheless, prospective purchasers may be reluctant to acquire works through these channels due to the lack of information regarding their provenance and authenticity. In light of these considerations, it was proposed to implement blockchain technology in the system of dissemination and sales of works of art in the field of plastic arts at the National University of Loja with the objective of providing traceability to each work of art. In pursuit of our objective, we utilized the Agile Block Chain Dapp Engineering (ABCDE) methodology to systematically develop crucial components, including a smart contract, for integrating the technology into our existing system. Additionally, we evaluated to gauge the achievable level of traceability through the technology implementation, utilizing key performance indicators (KPIs) as evaluation metrics. The experimental results obtained indicate that each work of art was successfully tracked from its from its creation to its sale, reaching a percentage of 100 % traceability, which means that the information 100% traceability, which means that the information recorded in the Polygon zkEVM Cardona's Polygon zkEVM Cardona's testing network was accurate and complete, thus providing a verifiable and detailed verifiable and detailed history of its provenance. In conclusion, it has been established that incorporating blockchain technology into the state-of-the-art distribution and sales system can provide a complete solution. This is made possible by leveraging its fundamental characteristics, such as decentralization, immutability, and transparency, to ensure the trackability of art pieces. Keywords: blockchain, traceability, NFT, artwork, decentralized app.